The Effect of E-Service Quality and E-Trust on Consumer Loyalty through Consumer Satisfaction as Intervening Variables (Case Study on Shopee Users in Malang Regency) - Abd. Hakam; Nur Hidayati; Supriyanto Supriyanto (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of e-service quality and e-trust on consumer loyalty through customer satisfaction as an intervening variable. The population of this research is Shopee users in Malang Regency. In this study, the sampling technique used purposive sampling so that 80 respondents were determined. The data analysis method is descriptive quantitative. Quantitative analysis was performed using Smart PLS. In this study, the results show that e-service quality and e-trust have a significant effect on consumer satisfaction, consumer satisfaction has an effect on consumer loyalty, e-trust has an effect on consumer loyalty, while e-service quality has no effect on consumer loyalty. Consumer satisfaction is not able to mediate the effect of e-service quality and e-trust on consumer loyalty.